A COMPARATIVE FEM ANALYSIS OF DRAGON SKIN ELASTOMERS FOR OPTIMIZING SOFT PNEUMATIC ACTUATOR PERFORMANCE - Yumna Memon; Saifullah Samo; Aamir Shaikh; Imran Ali Bhand; Safiullah Samo; Muhammad Ali Soomro (Spectrum of Engineering Sciences, 2025)
Soft pneumatic actuators are essential in soft robotics; their bending behavior depends on the non-linear characteristics of hyperelastic materials. Analytical models often cannot predict this performance accurately; computational techniques are needed for reliable results. The finite element method was used to quantitatively assess soft pneumatic actuators made from Dragon Skin 10 and Dragon Skin 30; both tested under the same pressurized loading. The research focused on understanding the trade-offs between achieving maximum bending and maintaining structural strength. Dragon Skin 10, which is more flexible, produced a maximum displacement of 0.161 m; Dragon Skin 30, which is stiffer, reached 0.092 m under identical conditions. Both materials experienced a peak von-Mises stress of about 1.37 x 10⁵ Pa, showing that the stress response was similar regardless of flexibility. However, the greater bending of Dragon Skin 10 came with a much higher maximum equivalent strain of 0.565, while Dragon Skin 30 stayed at 0.204. These results highlight that using softer materials can increase actuator motion but brings the material closer to its strain threshold, which could affect durability. Conversely, stiffer materials like Dragon Skin 30 provide more structural strength and a larger margin of safety, making them better for applications that demand accuracy and long-term use. The findings present a practical framework for material selection in soft pneumatic actuator design, allowing engineers to match material properties with specific performance needs and application requirements. The study supports informed decision-making for optimizing soft robotic systems.